Rumah Tangga Pra Sejahtera, Kebudayaan Kemiskinan, dan Program Penanggulangan Kemiskinan (Studi di Desa Munggu Kecamatan Bungkal Kabupaten Ponorogo) - Regina Rahma Pramudyani; Sugeng Harianto (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study examines the socio-economic conditions of pre-prosperous households, the practices of the culture of poverty, adaptive strategies for coping with poverty, and the effectiveness of poverty alleviation programs in Munggu Village, Bungkal District, Ponorogo Regency. This research employed a qualitative approach using participatory observation, unstructured interviews, and documentation techniques. The research subjects were selected through purposive sampling and consisted of ten pre-prosperous households receiving social assistance in Munggu Village. Data were analyzed through the stages of data reduction, data display, and conclusion drawing and verificationThe findings reveal four major points. First, the socio-economic conditions of pre-prosperous households in Munggu Village are characterized by unstable incomes derived from traditional agriculture and informal employment, low educational attainment, and inadequate housing conditions. Second, the culture of poverty is manifested through fatalistic and resigned attitudes, a short-term life orientation, dependence on social assistance, the intergenerational transmission of poverty, and declining life expectations, all of which are consistent with Lewis's concept of the culture of poverty. Third, the adaptive strategies adopted by these households include livelihood diversification, strict household expenditure management, the utilization of social networks through informal borrowing and lending practices, reliance on social assistance as a buffer for meeting basic needs, and the adoption of a modest lifestyle. Fourth, poverty alleviation programs, including the Family Hope Program (PKH), Direct Cash Assistance (BLT), and Social Welfare Assistance (Kesra), have proven effective in providing short-term benefits for fulfilling basic needs and supporting children's education. However, these programs have not been able to transform the structural conditions of poverty because they remain predominantly charitable in nature and have yet to address sustainable economic empowerment.